2022
DOI: 10.1007/s11356-022-22743-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of climate change on the agricultural economy in Thailand: an empirical study using panel data analysis

Abstract: This study estimates the impact of climate change on the economic growth of the agricultural sector and its variability using a panel dataset from 1995 to 2019 for 76 provinces in Thailand. The panel data analysis consists of unit root tests for identifying stationary characteristics, autoregressive distributed lag (ARDL) bounds for analyzing cointegration, and pool mean group (PMG) estimation for detecting long-run and short-run effects. The cointegration results indicate the existence of long-run equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The study results also showed that climate change reduced agricultural economic growth in the short run, however, in the long run, climate change has a positive impact on agricultural economic growth. A study on agricultural economic growth and climate change in Thailand from 1995 to 2019 using the ARDL bounds approach showed that temperature had a negative impact on the agricultural economy, while rainfall was positively associated with growth in the agricultural economy [125]. In a study using the ARDL approach looking at agriculture, climate change, and economic growth from 1971 to 2020 in Bangladesh, the study concluded that climate change had no impact on economic development [90].…”
Section: Discussionmentioning
confidence: 99%
“…The study results also showed that climate change reduced agricultural economic growth in the short run, however, in the long run, climate change has a positive impact on agricultural economic growth. A study on agricultural economic growth and climate change in Thailand from 1995 to 2019 using the ARDL bounds approach showed that temperature had a negative impact on the agricultural economy, while rainfall was positively associated with growth in the agricultural economy [125]. In a study using the ARDL approach looking at agriculture, climate change, and economic growth from 1971 to 2020 in Bangladesh, the study concluded that climate change had no impact on economic development [90].…”
Section: Discussionmentioning
confidence: 99%
“…In the model, CP shows cereal production (Metrics tons) (Pickson et al, 2020;Rehman et al, 2021;Chandio et al, 2023); CO2 refers to per capita CO2 emissions (metric tons) as an indicator of climate change (Adzawla et al, 2019;Adam & Drakos, 2022); The RF specifies the average annual rainfall (mm) as an indicator of climate change (Alagidede et al, 2016;Castro et al, 2020); TP shows the annual average temperature (Celsius) as an indicator of climate change (Jatuporn & Takeuchi, 2023); LCP refers to the cereal production area (Pickson et al, 2020;Chandio et al, 2023); DC is domestic credit to private sector by banks (% of GDP) as banks' domestic credit .…”
Section: Model and Datamentioning
confidence: 99%
“…Thailand and Malaysia's emerging economies in Southeast Asia face increasingly severe climate impacts due to their geographic location having long coastal lines and the majority of populations' livelihood depending on agricultural activities (Alam et al, 2012;Austin and Baharuddin, 2012;Tang, 2019;Jatuporn and Takeuchi, 2023). Both countries are parties to the UNFCCC and are committed to communicating their Nationally Determined Contributions (NDCs) every five years, starting in 2020.…”
Section: Introductionmentioning
confidence: 99%